Auditoría de Gestión al Departamento de Crédito y Cobranza de la Cooperativa de Ahorro y Crédito Coca Ltda. Agencia Loreto, período 2021. - Agreda Chongo, Sonnya Cándida (2023)
The objective of this degree project is to conduct a management audit of the Credit and Collection Department of Cooperativa de Ahorro y Crédito Coca Ltda, Agency Loreto, period 2021, it was determined the existing problems in the operational area and its impact on the percentage of overdue portfolio such as the lack of evaluations to internal processes and the lack of follow-up to debtor members, in the methodology that was applied was used the descriptive type, supported by the deductive method; Once the management audit phases were applied, it was possible to know that they have a regulation that governs the process of granting and recovery of funds, those responsible for each activity were defined, regarding the internal control system it was determined that they have a confidence level of 76% high and a risk of 24% low, within the specific planning phase it was established; in credits a risk of 37%, portfolio recovery of 17% and in the administration of human talent it reached 57% being its main weakness; While the management indicators have not been applied and the degree of compliance with the objectives set by the organization is not met in full, mainly due to the absence of strategies to improve the performance of the cooperative, lack of supervision to the processes of credit and recovery of overdue portfolio, nor has the performance of employees of the credit and collection department been evaluated; it is recommended the socialization of the processes and procedures defined for the credit and collection department based on the current regulations and a training of the functions manual so that the activities are carried out fulfilling the necessary activities directed to the administration, a monitoring plan of the activities and Management indicators should be made to measure the levels of efficiency and effectiveness in the use of the resources of the cooperative, considering that it is the essential activity to be developed in the cooperative to take corrective measures in time.